(untitled) (Architecture Image Studies, 2026)
The rapid digital transformation in the logistics industry has accelerated the adoption of mobile applications to improve service efficiency and user experience. Despite technological advances, user adoption of the SiCepat Ekspres mobile application in Indonesia remains stagnant, indicating a gap between innovation and user acceptance. This study extends the Unified Theory of Acceptance and Use of Technology (UTAUT) by integrating Task-Technology Fit (TTF) and Trust to analyze mobile application adoption in the logistics industry. A survey of 620 users was analyzed using Structural Equation Modeling (SEM-PLS), showing that performance expectancy, effort expectancy, social influence, and facilitating conditions significantly influence behavioral intention. Furthermore, task-technology fit and trust are key factors that drive both behavioral intention and use behavior. These findings contribute to the technology adoption literature and provide strategic recommendations for enhancing user trust through system reliability and a smoother user experience, ensuring higher engagement and long-term adoption.